Analysis of square concrete-filled cold-formed steel Tubular Columns Under axial cyclic loading - Chinnapat Buachart (2018)
© Int. J. of GEOMATE. This research studied the behavior of the square concrete-filled cold-formed steel tube (CFST) columns under axial cyclic loading. A total of 9 specimens were tested. All tested specimens are 75×75 millimeter square tube section. The parameters varied in the test are the thickness of steel tube, the compressive strength of filled concrete, and specimen length. The values of tube thickness are 1.8 and 3 millimeters. The column lengths are 500 and 1000 millimeters. In-filled concrete compressive strengths are 0 (unfilled), 20 and 40 MPa, respectively. Then the experimental strengths were compared with the design strengths computed from various international design codes. Finally, the specimens were analyzed by finite element software. The analytical results showed fairly close agreement with experimental results in terms of buckling mode, load-deformation response, the tension capacity and the decreasing compression capacity under cyclic load.